Analisis Partisipasi Masyarakat dalam Membayar Pajak Bumi dan Bangunan (Studi Kasus Desa Puhpelem) - Murnita Wahyu Agustin; Ardyan Firdausi Mustoffa (Politeknik Ganesha Medan, 2023)
This study aims to determine community participation in paying Land and Building Tax, including to find out the elements of opportunity, willingness, and ability of village communities to pay Land and Building Tax. Qualitative descriptive method was applied in this study with primary data sources. Direct interviews were carried out with village officials and village tax payers to obtain the necessary data. The results of the study show that community participation can grow and develop based on three main elements, including opportunities that are wide open for the community to participate in paying Land and Building Tax in Puhpelem Village, this means that the SPPT has been submitted to taxpayers in a timely manner by the Village Office Pupelem, the lack of willingness of the Pupelem Village community to pay taxes is not only caused by economic factors, but also caused by SPPT which contains incorrect data listed. In paying land and building tax, the ability of the people of Puhpelem Village is said to be good.